Can National Forest Cities Construction promote Urban Sustainability and Resilience? Evidence from a quasi-natural experiment in China - Jiang, Song; Yin, Jianhui; Jiang, Yu (Frontiers in Ecology and Evolution, 2025)
With the rapid acceleration of global urbanization, Urban Sustainability and Resilience (USR) have emerged as pivotal issues in addressing resource scarcity, environmental degradation, and extreme climate challenges. Focusing on this context, this study investigates whether the National Forest Cities Construction (NFCC) policy promotes urban sustainability and resilience and examines how human capital (HC), artificial intelligence (AI) and government support (GS) mediate these effects. This study evaluates the impact of National Forest Cities Construction (NFCC) policies on USR using panel data from 300 Chinese cities from 2000 to 2023. Employing a multi-period Difference-in-Differences (DID) approach and constructing an entropy-weighted TOPSIS evaluation framework, we systematically assess the policy effects on urban economic, social, and environmental coordination and risk response capacities. Our findings reveal a significant positive impact of NFCC policies on overall USR, with pronounced heterogeneous effects observed across regions and city scales—most notably, policies exhibit the strongest effects in eastern regions and are particularly sensitive among small-to-medium-sized cities. Further mechanism analyses identify three intrinsic transmission pathways: Human Capital (HC), Artificial Intelligence (AI), and Government Support (GS). Although the HC channel initially displays a negative adjustment effect, the gradual accumulation of skilled talent significantly enhances its positive influence over time. In contrast, while the AI channel effectively promotes intelligent technology adoption, it negatively affects Urban Sustainability (US) yet positively contributes to Urban Resilience (UR). The GS channel significantly increases public financial investment and environmental governance; however, inefficiencies in resource allocation yield negative transmission effects on both US and UR. These empirical insights clarify the effectiveness of NFCC policies and their regional and scale-specific differences, offering practical recommendations for policy optimization and governance strategies. Ultimately, this study provides a robust theoretical and empirical foundation for advancing high-quality urban development characterized by integrated economic growth, environmental protection, and risk management.